Vitamin D Deficiency and Its Association With Anemia and Blood Transfusion Requirements in Nigerian Adults With Sickle Cell Anemia. (October 2021) - Ochogwu, Olanrewaju Lauretta; Salawu, Lateef; Owojuyigbe, Temilola Oladunmomi; Adedeji, Tewogbade Adeoye
Background: Vitamin D supplementation has been shown to improve hemoglobin levels in patients with sickle cell anemia (SCA). However, very little is known about the prevalence of its deficiency, its role in hemolysis, and its effects on transfusion requirements in SCA, hence this study. Patients and Methods: Serum level of vitamin D was determined in 50 SCA patients in steady state, 50 SCA patients in hemolytic crises, and 50 in normal HbAA individuals. All were 18 years or older and were age- and sex-matched. In addition, PCV and hemoglobin (Hb) concentration, absolute reticulocyte count, uric acid, total and conjugated bilirubin, creatinine, lactate dehydrogenase (LDH), and estimated glomerular filtration rate (eGFR) were also assessed in all subjects and controls. Baseline sociodemographic, clinical, and anthropometric data were also recorded. Results: The prevalence of vitamin D insufficiency and deficiency was found to be 18% and 79%, respectively. The mean serum levels of vitamin D were 18.84 ± 6.86 ng/mL and 17.58 ± 6.23 ng/mL in the steady-state and the hemolytic crises SCA groups, respectively. Transfusion requirements were found to be higher in SCA patients with lower vitamin D levels. Unlike those in crisis who received one or more units of blood transfusion, 42% of those in the steady state did not receive blood transfusion over the same period of 12 months. Hemoglobin levels were, however, found to predict reduced vitamin D levels. Conclusion: Vitamin D deficiency (VDD) is highly prevalent among adults with SCA and those with lower vitamin D levels are more anemic and hence may require more blood transfusions.